1993
DOI: 10.1143/jjap.32.l180
|View full text |Cite
|
Sign up to set email alerts
|

A High Current Gain Si Metal Insulator Semiconductor Tunnel Emitter Transistor

Abstract: The mixing process is a crucially important stage in the operation of biological and chemical microfluidic devices. If the mixing is inadequate, reactants do not fully interact with each other, and the device may not operate properly. This paper describes a simplified microfluidic mixer (different from a chaotic mixer) which can uniformly mix a buffer solution with living cells by applying an AC electric charge. Diffusion of the living cells into the buffer solution occurs rapidly following the interface of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…For the oxide films grown under similar conditions, the SiO 2 thickness deviation was estimated as σ d ∼ 2 Å using the transmission electron microscope (for a reference, the SiO 2 monolayer thickness equals 3.1 Å [1]). At the qualitative level, the behaviour of studied devices was similar to the theoretical prediction for it and to the independent data of other authors [7][8][9][10][11]. The stability and reproducibility of characteristics were sufficient for reliable measurements.…”
Section: Experimental Samplessupporting
confidence: 85%
See 1 more Smart Citation
“…For the oxide films grown under similar conditions, the SiO 2 thickness deviation was estimated as σ d ∼ 2 Å using the transmission electron microscope (for a reference, the SiO 2 monolayer thickness equals 3.1 Å [1]). At the qualitative level, the behaviour of studied devices was similar to the theoretical prediction for it and to the independent data of other authors [7][8][9][10][11]. The stability and reproducibility of characteristics were sufficient for reliable measurements.…”
Section: Experimental Samplessupporting
confidence: 85%
“…In a field-effect transistor, the tunnelling is a parasitic effect, but there are another elements-MOS photodiodes (e.g. [5]) and transistors with a tunnel MOS emitter [7][8][9][10][11][12]-whose operation is just based on the tunnelling through the oxide. Anyway, the charge transport through thin SiO 2 film requires careful consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Barrier height and effective masses of the electrons and holes control the current gain in case of direct tunneling. The main interest in the TEBT approach in recent years was an attempt to combine CMOS and bipolar technology using exactly the same device (2)(3)(4). In this work, it is proposed and demonstrated that the TEBT is a useful tool for characterizing and better understanding of the properties of metal insulator stacks, somewhat in line with Eitan et al (5) who have studied the conventional silicon -silicon dioxide structure.…”
Section: Introductionmentioning
confidence: 61%
“…Silicon MOS TEBTs exhibit high current gain (2)(3)(4), implying that the recombination velocity at the ideal Si-SiO 2 interface is very low. The TEBTs reported here exhibit some current gain, but not as high as in the silicon MOS case.…”
Section: Dielectric-semiconductor Interface Characterizationmentioning
confidence: 99%
“…. 10)m 0 [19]) and χ = χ h , was rejected, since it would lead to unrealistically small values of j h (both 'classical' and quantum) and would predict very large values of current gain ( 10 4 ) that are never observed experimentally [3,5,7,20].…”
Section: Parameter Setmentioning
confidence: 99%